The employer's prerogatives: to what extent the law entrenched under the IRA / Noor Aza Ahmad - Ahmad, Noor Aza (Faculty of Law, 1986)
In any industrial organisations there are two parties involve, the employer and the employees, where the employer is the owner. In the old days, the relationship between the employer and employees was known as the relationship of 'master' and 'servant', which was more strict than today.